KEPERCAYAAN MASYARAKAT TERHADAP RITUAL MEMINDAHKAN HUJAN DI DESA TUALANG KECAMATAN TUALANG KABUPATEN SIAK - Kurniadi Adha; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is a research about rain-moving ritual which is believed by society of Tualang Sub-district. This research is to find out about the implementation of rain-moving rituals and public confidence in rain-moving rituals. This type of research uses qualitative research type with descriptive analysis approach. The author uses field research (field research) with the form of non-participant observation (non participant observer). The author uses data collection techniques in the form of observation to produce data in accordance with reality and to obtain valid data about the role of rainmaster in carrying out its duties to prevent rain fall during the execution of the party took place. Interview (interview) to get information from the source about how the role of the rainy handler. Documentation for the addition of data in the form of photos and sound recordings. Based on the research that has been done, researchers get the results of research that is moving ritual rain done what if there are events such as weddings and circumcision events. public confidence in the rainy handler in dasari by the number of hajatan owned by the community so that in order to support these activities to run smoothly then used the rainy handler to resist the rain when the event held dienggrakan lasted.Keywords: Trust.Rain Charmer, rain-moving ritual.